HUBUNGAN KECANDUAN GAME ONLINE DAN KETERAMPILAN SOSIAL PADA PEMAIN GAME DEWASA AWAL DI JAKARTA BARAT - Stefani Virlia; Silvia Setiadji (Universitas Bunda Mulia, 2016)
Online game is a game that is loved by many people of ages ranging from children to adults. Online games can trigger addiction that can cause effects such as withdrawal, aggressiveness, problems in interpersonal relationships and can even lead to psychological disorders. This study aimed to examine the relationship between online gaming addiction and social skills in early adult game players. The method used is quantitative method and included into the type of correlational research. Respondents in this study is the online game players in the cafe Jakarta Barat, totaling 342 people. The results of this study revealed a significant correlation between addicted to online games and social skills in early adult game players with r = -0367 (p <0.05). Early adult game players have become addicted to the game because it makes online games as an escape from their problems. Keywords : addicted to online game; social skill;, early adulthood